REDESIGN PURWANTORO BUS STATION WITH GREEN ARCHITECTURE CONCEPT - Kurnianto, Ewang; Habsya, Chundakus; Nurhidayati, Aryanti (Pendidikan Teknik Bangunan, 2014)
ABSTRACTThe purpose of this study is ( 1 ) Designing Purwantoro Bus Station with Green Architecture concept. ( 2 ) Planing circulation passengers and bus so, comfortable and smooth so there is no mixing buses and passenger flows. ( 3 ) Designing the site so that all activities and passenger vehicles can run well for the present and future with green architecture concept. ( 4 ) Achieve the bus station environment refers to the Green Architecture .The study used a qualitative research. Primary data obtained from the observation of the research object. Secondary data is from records or documents obtained from Department of Transportation. Further data processing and analysis followed axisting condition bus station. Having completed the analysis existing then do analysis design concepts. The final step is designing new bus station.The results of this study indicate that: ( 1 ) Design of Purwantoro Bus Station using Green Architecture concept: (a ) Using solar cell roof were 112 pieces sollar cell to produce electricity for building manager 67000 watts used every day suplay of electric lighting Purwantoro Bus Station. ( b ) Use green roof on a building rooftop lounge area adds green space in the bus station. ( 2 ) The design and arrangement of the passenger and bus circulation in Purwantoro bus station is made easy, safe and convenient. ( 3 ) Site Purwantoro Bus Station designed to accommodate all activities according to the standard passenger vehicle and type of bus station by adding some space. ( 4 ) Design layout bus station using a mixture of patterns facilitate is to grouping of each function and the type of space and maximize green space in the bus station .Keyword: redesign, green architecture, green roof, solar cell.